2013
DOI: 10.1021/ef4019004
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Robust and Inexpensive Nanoporous TiO2 for Pre-combustion CO2 Separation

Abstract: The objective of this research is to study the performance of an inexpensive high-surface-area nanoporous titanium oxide (TiO 2 ) on the CO 2 /H 2 separation and resulting pre-combustion CO 2 capture. The experiments were carried out at different temperatures (25, 50, 75, 100, and 125 °C) and pressures (5, 10, 15, 20, 25, 30, and 35 bar) using a fixed-bed adsorber. The data obtained for the pure component isotherms and binary gas mixtures were correlated using Sips and Langmuir−Freundlich binary-component-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…found that ZrO 2 ‐supported potassium exhibits a higher CO 2 uptake, better thermal stability, and better regeneration characteristics than TiO 2 ‐supported potassium . Furthermore, the use of amine‐modified TiO 2 has been studied in CO 2 adsorption process by several research groups . More recently, Kapica‐Kozar and co‐workers modified bare TiO 2 with NH 4 OH and/or KOH solutions and found that the total adsorption capacity increased dramatically from 0.06 mmolCO2 g −1 in the case of bare TiO 2 to 0.53 mmolCO2 g −1 in case of the most efficient comodified sample (TiO 2 ‐2.5 % N/10 % K).…”
Section: Introductionmentioning
confidence: 99%
“…found that ZrO 2 ‐supported potassium exhibits a higher CO 2 uptake, better thermal stability, and better regeneration characteristics than TiO 2 ‐supported potassium . Furthermore, the use of amine‐modified TiO 2 has been studied in CO 2 adsorption process by several research groups . More recently, Kapica‐Kozar and co‐workers modified bare TiO 2 with NH 4 OH and/or KOH solutions and found that the total adsorption capacity increased dramatically from 0.06 mmolCO2 g −1 in the case of bare TiO 2 to 0.53 mmolCO2 g −1 in case of the most efficient comodified sample (TiO 2 ‐2.5 % N/10 % K).…”
Section: Introductionmentioning
confidence: 99%
“…High time resolution for composition measurement is desirable, especially for mixtures containing strongly adsorbing species with sharp breakthrough profiles. This makes the MS the most popular choice, although other sensors like infrared 36 or H 2 analyzers 37 have also been used.…”
Section: Breakthrough Methodsmentioning
confidence: 99%
“…Before adsorption started, N 2 was preferred to be introduced into the adsorber until pressure in the adsorber rose to a predetermined value and N 2 constant concentration profiles on the MS were observed. This was followed by closing the back-pressure regulator (21) and 3-way valve (8) to maintain constant pressure inside the adsorber, after which th e ou tl e t N 2 of the back-pressure regulator (13) between the back-pressure regulator (5) and (6) was maintained at the same set pressure through the back-pressure regulator (5). After the concentration of N 2 entering the MS gradually decreased to zero, the adsorbates were introduced into the adsorber to replace the filled N 2 until constant concentration profiles on the MS were observed by opening the back pressure regulator (21).…”
Section: Co 2 /Ch 4 Separation Proceduresmentioning
confidence: 99%
“…Intensive research interest has focused on the utilization of high surface areas and open pore solid sorbents for CO 2 capture. [3,7] Examples of porous inorganic materials include activated carbon [8,9], zeolites [10,11], silica [12], titanium dioxide [13], and metal-organic frameworks (MOFs) [14,15]. These sorbents are normally used in adsorption fixed bed reactors or fluidized bed reactors.…”
Section: Introductionmentioning
confidence: 99%